Transdermal insulin on demand - Smith, Fiona (2024)
In 2021, 537 million people worldwide had been diagnosed with diabetes mellitus (1). Of those cases, up to 10% are Type 1 diabetes mellitus (T1DM). T1DM is a life-long condition that occurs when the pancreas is unable to produce endogenous insulin, leading chronic hyperglycaemia. Whilst T1DM can be controlled with insulin replacement therapy, low adherence and compliance, often caused by the need to administer using hypodermic needles, increases the likelihood of long-term complications and a poor quality of life. Microneedles (MNs) offer the potential for discrete and painless drug delivery, whilst facilitating the transdermal delivery of complex drug molecules. Several classes of MN have been explored in the literature, however two were selected for this work. Polymeric MNs dissolve upon insertion into the skin, releasing the drug payload, offering a simple one-step application with reduced sharps hazards. Additionally, hollow MNs, which can be envisaged as miniature hypodermic needles, are well suited to the administration of liquid formulations. Currently, there is no approved MN device for the transdermal delivery of drugs, in part due to poor insertion and dosing consistency. Therefore, the hypothesis was that MNs could be designed and manufactured that would be suitable for use as drug delivery platform, reliably delivering the anticipated dose of insulin across the skin. Initially, a patent search using the terms ‘‘microneedle’ and ‘insulin’’ was conducted to gain a better understanding of progress in the field. Owing to the number of patents filed, it was clear that interest in MNs for the application of insulin remained. However, most patented devices lacked features that would be required for successful clinical translation and use. Next, several commercially available hollow MN devices (AdminPen™1500, AdminPen™900 and HydraNeedle20) underwent in vitro and ex vivo characterisation. Devices were generally manufactured to a poor standard, affecting the insertion in skin models. Permeation studies further supported this. Consequently, none of these devices were deemed appropriate for the delivery of insulin in T1DM. As such, bespoke polymeric and hollow insulin loaded MNs were designed, manufactured and evaluated. Polymeric MNs were manufactured using a two-step casting process during which insulin is loaded into the needle layer. A range of materials were explored for the needle layer (polyvinylpyrollidone-co-vinyl acetate (PVPVA), sodium carboxymethyl cellulose (CMC) and Soluplus®) and the backing layer (sodium CMC with glycerol, (poly(vinyl alcohol) PVA) and polystyrene). PVPVA was selected for the needle layer owing to maintaining insulin stability and its favourable insertion profile. MNs manufactured with a PVA backing layer demonstrated an improved insertion efficiency however, through use of a fluorescently tagged insulin, it was identified that the sodium CMC backing layer promoted tip loading of insulin. Permeation studies found that the PVA backing layer offered an overall advantage in insulin delivery. This work highlighted the importance of the backing layer as it had a significant impact on the insertion of MNs. Later, custom-made single 1 mm hollow MNs were designed and manufactured by taking a 4 mm 31-gauge hypodermic needle and attaching a 3D-printed component. Several techniques were employed to improve the insertion depth and reduce variability, including the angle of insertion and application of strain to skin. Later, a DermaPen™ device was modified to incorporate a single hollow MN, capable of delivering insulin whilst oscillating. High-speed oscillation demonstrated a good insertion depth with reduced variation compared to the other approaches tested. Histological staining suggested that elastin fibres in the skin were disrupted, reducing the viscoelasticity and improving the insertion. Permeation studies demonstrated improved insulin delivery when oscillation was employed compared to administration of insulin via a static MN. Orbi-SIMS analysis further confirmed the successful delivery of insulin into the skin. In conclusion, both a polymeric MN array loaded with insulin and an oscillating single hollow MN have been manufactured and demonstrated the successful transdermal delivery of insulin. Moreover, information on mechanisms that can be incorporated into MN devices to improve the consistent MN insertion and delivery of insulin have been elucidated.